Nikki Tesla and the fellowship of the bling - Keating, Jess (Keating, Jess. Elements of genius, 2020)
"When Mary Shelley is kidnapped by a mad scientist, Nikki Tesla and the other members of the Genius Academy team are forced to agree to steal a priceless, lethal high-tech ring in order to free her; but Nikki also plans to use the heist to get closer to her long-lost father who claims he is not the criminal mastermind she believes him to be." --